The role of business size in assessing the uptake of health promoting workplace initiatives in Australia - A. W. Taylor; R. Pilkington; A. Montgomerie; H. Feist (BMC, 2016)
Abstract Background Worksite health promotion (WHP) initiatives are increasingly seen as having potential for large-scale health gains. While health insurance premiums are directly linked to workplaces in the USA, other countries with universal health coverage, have less incentive to implement WHP programs. Size of the business is an important consideration with small worksites less likely to implement WHP programs. The aim of this study was to identify key intervention points and to provide policy makers with evidence for targeted interventions. Methods The worksites (n = 218) of randomly selected, working participants, aged between 30 and 65 years, in two South Australian cohort studies were surveyed to assess the practices, beliefs, and attitudes regarding WHP. A survey was sent electronically or by mail to management within each business. Results Smaller businesses (<20 employees) had less current health promotion activies (mean 1.0) compared to medium size businesses (20-200 employees - mean 2.4) and large businesses (200+ employees - mean 2.9). Management in small businesses were less likely (31.0 %) to believe that health promotion belonged in the workplace (compared to 55.7 % of medium businesses and 73.9 % of large businesses) although half of small businesses did not know or were undecided (compared to 36.4 and 21.6 % of medium and large businesses). In total, 85.0 % of smaller businesses believed the health promotion activities currently employed in the worksite were effective (compared to 89.2 % of medium businesses and 83.1 % of large businesses). Time and funding were the most cited responses to the challenges to implementing health promoting strategies regardless of business size. Small businesses ranked morale and work/life balance the highest among a range of health promotion activities that were important for their workplace while work-related injury was the highest ranked consideration for large businesses. Conclusion This study found that smaller workplaces had many barriers, beliefs and challenges regarding WHP. Often small businesses find health promotion activities a luxury and not a serious focus of their activities although this study found that once a health promoting strategy was employed, the perceived effectiveness of the activities were high for all business regardless of size. Tailored low-cost programs, tax incentives, re-orientation of work practices and management support are required so that the proportion of small businesses that have WHP initiatives is increased.